Obesity is not a risk factor for either mortality or complications after laparoscopic cholecystectomy for cholecystitis - Yuta Enami (Nature Portfolio, 2021)
Abstract Obesity is a positive predictor of surgical morbidity. There are few reports of laparoscopic cholecystectomy (LC) outcomes in obese patients. This study aimed to clarify this relationship. This retrospective study included patients who underwent LC at Showa University Northern Yokohama Hospital between January 2017 and April 2020. A total of 563 cases were examined and divided into two groups: obese (n = 142) (BMI ≥ 25 kg/m2) and non-obese (n = 241) (BMI < 25 kg/m2). The non-obese group had more female patients (54%), whereas the obese group had more male patients (59.1%). The obese group was younger (56.6 years). Preoperative laboratory data of liver function were within the normal range. The obese group had a significantly higher white blood cell (WBC) count (6420/μL), although this was within normal range. Operative time was significantly longer in the obese group (p = 0.0001). However, blood loss and conversion rate were not significantly different among the groups, neither were surgical outcomes, including postoperative hospital stay and complications. Male sex and previous abdominal surgery were risk factors for conversion, and only advanced age (≥ 79 years) was an independent predictor of postoperative complications as observed in the multivariate analysis. Although the operation time was prolonged in obese patients, operative factors and outcomes were not. Therefore, LC could be safely performed in obese patients with similar efficacy as in non-obese patients.